Smart bin for wet waste detection using ESP8266 NodeMCU / Siti Nur Athirah Ab Hamid - Ab Hamid, Siti Nur Athirah (2020)
Waste management is one of the primary problems that happen in current urbanization in the world, including Malaysia. As we can see today in Malaysia, the problem of waste disposal does not move along with the contemporary urban modernization, and this issue has become increasingly. Although the smart waste bin technology is already available, not all have a thoroughly perfect function. To overcome these situations, an efficient smart waste bin has to be developed. The objectives of this project are to develop a prototype of smart waste bin for wet waste and to evaluate the performance of ultrasonic and moisture sensors using ESP8266 NodeMCU. LEDs have been attached to the sensor for its function itself. The level of waste is monitored using the ultrasonic sensor, and a red LED will turn on when the waste reaches the threshold of the bin. The moisture sensor will measure the percentage of moisture content, and a green LED will light up. Two main tests have been conducted to identify the objective of the project, which are functionality and usability testing. It requires to measure the detection of the sensor with its capability and functionality. ESP8266 NodeMCU been connected to Wi-Fi connection which is mobile phone hotspot. Mobile phone was placed 10 meters far from the devices to see the performances of the mobile hotspot which is mobile phone. The tests revealed that the project is behaving accordingly and achieved its objective and is usable to the user and positive feedback received through the questionnaire.